Acrylic adhesives in the polyolefins joining - Pinto, A. M. G. (2014)
The mechanical behaviour of single lap adhesive joints was characterized, using two commercial acrylic adhesives. For this purpose the surfaces were cleaned and abraded using fine grit abrasives. The effect of temperature and moisture in the mechanical strength was, also, evaluated. For this characterization, mechanical tests were carried out according procedure and geometry foreseen by ASTM D3163-01 [1] and ASTM D4501-01 [2] standards. The results show that it is possible to get good strengths without great surface preparation. The temperature and moisture effect observed don’t seem to be relevant for the mechanical behaviour.